Challenges of Mastering English in Syria With Emphasis on Speaking: Suggested Remedies and Recommendations for Foreign Language Teaching - Farah Hijazi (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2023)
Pioneers of applied linguistics have spared no effort in theorizing and innovating fruitful techniques through which foreign languages should be both taught and mastered. In addition, a wave of research has been conducted to bring English language teaching inadequacy to light. It is because we are now on a threshold of a new age that mastering at least one foreign language, say English, has become an urgent need. But why English? English is the language of most manuals, the medium of instruction at many virtual or physical institutions throughout the world, of instructional programs, and of international conferences. News presentation or conference interpretation is mostly provided in English. Among other languages, English has long enjoyed an advantage. However, Arab learners of English, notably Syrians, show deficiency when communicating in English, which, in their setting, is merely a foreign language. This might be attributed to many factors related to teachers’ teaching styles, governmental curricula or courses design, lessons allotment and exams question type. This article addresses the methods employed in language teaching, the challenges of mastering English in the Syrian setting with emphasis on speaking and why many languages program fail to operate as needed. Furthermore, it recommends specific policies towards better teaching and learning practices. These recommendations, therefore, once implemented, are capable of impacting both national and international security. They may include teachers’ training program, new curricula design policies and lessons allotment where speaking is given more time for learners to practice the language. Additionally, programs for teachers should be developed to prepare them to use cutting-edge teaching strategies which take into account the different demands and styles of students. The training courses should also focus on enhancing instructors' abilities and expertise in the field of language instruction.